Vanillic acid protects mortality and toxicity induced by N-ethyl-N-nitrosourea in mice; in vivo model of chronic lymphocytic leukemia - Ahmad Salimi; Shadi Haddadi; Saleh Khezri; Bahare Asgari; Mahshad Pourgholi (Toxicology Reports, 2024)
Alkylating agents such as N-Ethyl-N-Nitrosourea (ENU) are ubiquitous within living cells and in the environment. This study designed to evaluate the chemopreventive activity of vanillic acid on ENU-induced toxicity and carcinogenesis in mice as an animal model of chronic lymphocytic leukemia (CLL). The female, Swiss albino mice were divided into three groups each with 7 mice, group I received normal saline, group II, mice received ENU at a dose of 80 mg/kg body weight i.p. to induce CLL on the 31th day of the study, and group III, the mice pretreated with vanillic acid at a dose of 20 mg/kg body weight/day, i.p. up to 30 days and received ENU. The animals were monitored for weight changes and mortality during 120 days, and then were sacrificed for isolation of lymphocytes, as target cells in CLL. Cellular parameters like reactive oxygen species (ROS) formation, malondialdehyde (MDA) production, depletion of glutathione (GSH), mitochondrial membrane potential (MMP) and lysosomal membrane integrity were studied. We found that pretreatment with vanillic acid significantly increased the survival of mice up to 57%, delay in death time (30%) and prevented weight changes after exposure to ENU. In addition, it was found that vanillic acid protected ROS formation, lipid peroxidation mitochondrial dysfunction, and lysosomal membrane destabilization in isolated lymphocytes. These data suggest that vanillic acid exhibited significant protection against ENU-induced toxicity and carcinogenicity, which might be related to the protection of the mitochondria and lysosomes and the reduction of ROS formation and oxidative stress.